Gpnmb Is a Potential Marker for the Visceral Pathology in Niemann-Pick Type C Disease - Marques, André R. A.; Gabriel, Tanit L.; Aten, Jan; van Roomen, Cindy P. A. A.; Ottenhoff, Roelof; Claessen, Nike; Alfonso, Pilar; Irún, Pilar; Giraldo, Pilar; Aerts, Johannes M. F. G.; van Eijk, Marco (PloS one, 2016)
Impaired function of NPC1 or NPC2 lysosomal proteins leads to the intracellular accumulation of unesterified cholesterol, the primary defect underlying Niemann-Pick type C (NPC) disease. In addition, glycosphingolipids (GSLs) accumulate in lysosomes as well. Intralysosomal lipid accumulation triggers the activation of a set of genes, including potential biomarkers. Transcript levels of Gpnmb have been shown to be elevated in various tissues of an NPC mouse model. We speculated that Gpnmb could serve as a marker for visceral lipid accumulation in NPC disease. We report that Gpnmb expression is increased at protein level in macrophages in the viscera of Npc1nih/nih mice. Interestingly, soluble Gpnmb was also found to be increased in murine and NPC patient plasma. Exposure of RAW264.7 macrophages to the NPC-phenotype-inducing drug U18666A also upregulated Gpnmb expression. Inhibition of GSL synthesis with the glucosylceramide synthase (GCS) inhibitor N-butyl-1-deoxynojirimycin prevented U18666A-induced Gpnmb induction and secretion. In summary, we show that Gpnmb is upregulated in NPC mice and patients, most likely due to GSL accumulation.